2016
DOI: 10.1111/nhs.12259
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of instructor‐led versus peer‐led debriefing in nursing students

Abstract: Despite its widespread support, the most effective simulation-based debriefing method has little evidence to support its efficacy. In this study, we compared the effect of peer-led and instructor-led debriefing among nursing students. The study was conducted with a non-equivalent control group using a pretest-post-test design. A convenience sample of third-year nursing students was used for the study, where 65 students enrolled in a 2-week clinical placement rotation were randomly assigned to the instructor-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 37 publications
0
39
0
4
Order By: Relevance
“…ey found a general mismatch between what the instructors claimed was important in CPR education and what they actually did. In other studies, findings have shown that self-directed learning was better than instructor-led learning [15], training with voice advisory manikins (VAM) was better than instructorled training [4], and the debriefing after CPR was better if it was instructor-led than peer-led [16].…”
Section: Introductionmentioning
confidence: 99%
“…ey found a general mismatch between what the instructors claimed was important in CPR education and what they actually did. In other studies, findings have shown that self-directed learning was better than instructor-led learning [15], training with voice advisory manikins (VAM) was better than instructorled training [4], and the debriefing after CPR was better if it was instructor-led than peer-led [16].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly‐used method is facilitator‐guided post‐event debriefing (Sawyer et al ., ). Among nursing students, instructor‐led debriefing is a more effective method in improving skills performance compared with peer‐led debriefing (Roh, Kelly, & Ha, ). However, challenges include limited/no designated space for debriefing, large class sizes, complex scheduling, and lack of time (Waznonis, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although CPR training is a core competence in Korea, there is a deficiency in faculty training for undergraduate CPR education. Nursing students who underwent instructor‐led debriefing were more effective in improving CPR skills compared to peer‐led debriefing (Roh et al ., ). Faculty development is a priority because the instructor's expertise and the debriefing process are important to achieve optimal learning.…”
Section: Discussionmentioning
confidence: 97%
“…A systematic review reported moderate–large effects favoring technology‐enhanced, simulation‐based training for satisfaction, and small effects for knowledge, process skill, and time outcomes compared with other instructional modalities (Mundell et al ., ). During two rescuer adult BLS, nursing students in the instructor‐led debriefing group showed better subsequent performance, higher satisfaction with simulation experience, and increased debriefing quality scores compared to the peer‐led group (Roh et al ., ). Curricula should be designed to enable nursing students to learn the concepts, principles, and procedures of CPR.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation